The Arab Peculiarity of Jorge Amado (London Journal of Research In Humanities and Social Sciences, 2025)
This article deals with the study of Arabic settings in the work of Jorge Amado. To this end, we choose as privileged texts of this research the twenty-four novels published by the author, where we seek to observe the similarities and differences in the representations of the Arab immigrant, as well as the lines responsible for configuring the Arab-Brazilian identity of southern Bahia, woven by the interrelationship between the cultural features of the Sertanejo and the cultural features of the Arabs, both expelled from their lands, by necessity or by wars. As a methodological theoretical reference, we will avail ourselves of Edward Said’s contributions to understanding the Arab universe in the West; Alice Raillard’s studies of the Baian writer’s aesthetic choices; and the author’s own confessions about his literary making.
Keywords: Arab immigration; Brazilian identity; Brazilian literature; Orientalism